Career exploration fair - Chiko, Carl H.; Marks, Stephen E. (Canadian Journal of Counselling and Psychotherapy, 2012)
The career exploration fair is a collaborative community project designed to promote career exploration. The fair provides students with direct exposure to a variety of occupations and brings the notion of career development into focus. In addition to its educational benefits the fair is a vehicle for the school and the community to work together as equal partners in the development of the community and its youth.